Why COVID-19 strengthens the case to scale up assault on non-communicable diseases: role of health professionals including physical therapists in mitigating pandemic waves - Elizabeth Dean; Margot Skinner; Homer Peng-Ming Yu; Alice YM Jones; Rik Gosselink; Anne Söderlund (AIMS Press, 2021)
As SARS-CoV-2, the virus responsible for COVID-19, spread globally, the most severely affected sub-populations were the elderly and those with multi-morbidity largely related to non-communicable diseases (NCDs), e.g., heart disease, hypertension, type 2 diabetes, obesity. NCDs are largely preventable with healthy nutrition, regular activity, and not smoking. This perspective outlines the rationale for health professionals' including physical therapists' role in reducing COVID-19 susceptibility. Evidence is synthesized supporting the pro-inflammatory effects of the western diet, increasingly consumed globally, inactivity, and smoking; and the immune-boosting, anti-inflammatory effects of a whole food plant-based diet, regular physical activity, and not smoking. An increased background of chronic low-grade systemic inflammation associated with unhealthy lifestyle practices appears implicated in an individual's susceptibility to SARS-CoV-2. It is timely to re-double efforts across healthcare sectors to reduce the global prevalence of NCDs on two fronts: one, to reduce SARS-CoV-2 susceptibility; and two, to reduce the impact of subsequent waves given high blood pressure and blood sugar, common in people with multi-morbidity, can be improved within days/weeks with anti-inflammatory healthy lifestyle practices, and weight loss and atherosclerosis reduction/reversal, within months/years. With re-doubled efforts to control NCD risk factors, subsequent waves could be less severe. Health professionals including physical therapists have a primary role in actively leading this initiative.